Alternative ventilation strategies in U.S. offices: Saving energy while enhancing work performance, reducing absenteeism, and considering outdoor pollutant exposure tradeoffs. (1st May 2017) - Ben-David, Tom; Rackes, Adams; Waring, Michael S.
Abstract: Mechanical ventilation can improve occupant productivity, use or save energy, and increase outdoor-to-indoor pollutant transport. This work explores those impacts for eight ventilation strategies, relative to a baseline constant mechanical ventilation rate (VR) of 9.4 L/s/occ, in two representative offices. Strategies were unique combinations of airside economizing, demand-controlled ventilation, and supply air temperature reset, along with doubling the baseline VR. These were evaluated within a Monte Carlo analysis that varied climate and outdoor pollution, along with 19 building parameters. Energy modeling, empirical correlations, and indoor air quality (IAQ) modeling were used to quantify outcomes of: ( i ) energy use; ( ii ) profitable IAQ impacts, e.g. work performance; and ( iii ) negative IAQ health impacts due to indoor particle and ozone exposure. 'Win-win' strategies were defined as those that saved energy and increased work performance, and these always included an economizer. Relative to the baseline, the win-win strategies: increased annual geometric mean VRs by 5–10 L/s/occ; reduced mechanical system energy consumption by 12–27% (saving $1–1.75/m 2 /year); increased work performance by 0.5%; eliminated 5 h of absenteeism per year; and increased indoor PM2.5 by 0.5 μg/m 3 and ozone by 3 ppb. A sensitivity analysis identified infiltration and climate as the largest outcome drivers. Median annual benefits for small-to-medium-large offices in the U.S. (∼75% of office floorspace) were $28 billion for implementing the win-win strategy with the greatest energy savings, and $55 billion for implementing the win-win strategy with the greatest work performance increase. Particle exposure tradeoffs were mitigated by use of efficient filters. Highlights: Two office types were modeled using a wide array of building parameters and environments. Each instance was simulated under a baseline ventilation strategy and 6–8 alternative strategies. Strategies that both saved energy and increased work performance always included an economizer. Win-win strategies also reduced absenteeism and SBS symptoms, but increased indoor exposure to PM2.5 and ozone. The sector-wide benefits were twice as large when work performance was optimized rather than energy use.